THE RELATIONSHIP BETWEEN PERCEIVED PARENTING PRACTICES AND WELL-BEING AMONG YOUNG ADULT FEMALES IN TURKEY - Wise, Ryan Macey; Erbahar, Aylin (Editura Univ Oradea, 2021)
The family in modern Turkey faces a challenge in balancing the traditional collective value system that emphasizes the group over the individual, while also integrating a greater push toward self-expression and autonomy among young adults. Providing autonomy support within the relational bonds of the family represents a challenge for the collectivistic oriented family in Turkey. The focus of this study was to examine this problem through an analysis of parenting practices and their influence on emerging adult well-being in the context of cultural change. A non-random convenience sample of 238 female emerging adults living in Istanbul, Turkey, reported on their mothers' and fathers' parenting practices and their own psychological well-being. A series of multiple regression analyses explored the predictive strength of parenting practices. For mothers, the most consistent predictor of participant well-being was autonomy support, while for fathers it was emotional warmth. Participants indicated mothers were more involved and provided more autonomy support than did fathers. Parental involvement was not significantly related to any well-being measure. Significantly higher optimism and life satisfaction was found for participants identifying as an adult. The results are suggestive of the emergence of a new fathering role in urban middle-SES families. Mother and father warmth scores were not perceived to be different, but father warmth was predictive of well-being, indicating both a transition away from traditional authoritarianism and toward a greater emotionally-present democratic parenting style. These novel findings are interpreted as a reflection of a change in fathering related to mothering.
Keywords: Emerging Adulthood; Well-Being; Parenting; Autonomy; Self-Determination Theory; Father Involvement; Autonomy Support; Family; Relatedness; Mothers; Anxiety; Warmth; Transition; Depression